2021
DOI: 10.1021/acs.chemmater.0c04097
|View full text |Cite
|
Sign up to set email alerts
|

Layered Perovskite Doping with Eu3+ and β-diketonate Eu3+ Complex

Abstract: Metal halide perovskites are attracting great interest for the fabrication of light-emitting devices encompassing light-emitting diodes, lasers, and scintillators. As the field develops, perovskite doping emerges as a promising way to enrich the material functionalities and enhance the luminescence yield and tunability. While Mn +2 addition has been well explored, doping with lanthanides has received less attention, even though their intense and line-like luminescence is interesting for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 53 publications
3
38
0
Order By: Relevance
“…In this work, no emission lines associated with the Pr 3+ ion are observed. However, carrier transfer to lanthanide can be exploited for the design of advanced optoelectronic materials for high purity lanthanide emission by doping with alternative lanthanide ions or an advisable molecular design . These materials can be further developed by virtue of crystal field modulation, which is very likely effective in the Pr-ExMP-PeNC system in case excited carriers are transferred to the dopant.…”
Section: Resultsmentioning
confidence: 99%
“…In this work, no emission lines associated with the Pr 3+ ion are observed. However, carrier transfer to lanthanide can be exploited for the design of advanced optoelectronic materials for high purity lanthanide emission by doping with alternative lanthanide ions or an advisable molecular design . These materials can be further developed by virtue of crystal field modulation, which is very likely effective in the Pr-ExMP-PeNC system in case excited carriers are transferred to the dopant.…”
Section: Resultsmentioning
confidence: 99%
“…Eu 3+ doping introduced ve sharp emission bands peaking at 576, 589, 611, 648, and 697 nm characteristic of the Eu 3+ intra-congurational transitions 5 D 0 / 7 F J (J ¼ 0-4) which appeared overlapped with the triplet emission. 88 The presence of all ve Eu 3+ transitions indicated strong deviations from the inversion symmetry due to strong octahedral distortion, the spatial arrangement of the nearest neighbors (e.g., organic cations), and the symmetry group of the crystal lattice. 88 The role of the NMA triplet was to sensitize the lanthanide material since Eu 3+ transitions were not observed in Eu doped BA 2 PbCl x Br 4Àx and PEA 2 PbCl x Br 4Àx systems where the organic cation does not have an accessible triplet level.…”
Section: A-site Doping Induced Optoelectronic Propertiesmentioning
confidence: 96%
“…85 88 The europium chelate doping was achieved by initially synthesizing the tetrakis bdiketonate complex Eu(tta) 4 P(Ph) 4 [Eu(L)], then the prepared complex was added to the spin coating solution to form the doped system NMA 2 PbBr 4 :Eu(L). 88 In both cases, the XRD diffraction peaks shied towards smaller angles indicating increase in interplanar spacing, which was explained by partial incorporation of chlorine in NMA 2 PbBr 4 :Eu and lattice expansion for NMA 2 PbBr 4 :Eu(L) due to the formation of an intercalation compound. The diffraction peak intensity decreased in NMA 2 PbBr 4 :Eu(L), indicating the reduction in crystallinity due to the introduction of the bulky Eu complex (Fig.…”
Section: B-site Dopingmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, rare earth ion (such as Eu 3+ and Sm 3+ ) doping is also widely used and a large number of high-performance perovskite luminescent materials have been obtained. However, due to the small reserves and high price of rare earth metals, their further application is limited. , Recently, some research showed that CsPb 2 Br 5 NCs have excellent water stability compared with CsPbBr 3 NCs. For example, Yao and his co-workers constructed the dual-phase CsPbBr 3 /CsPb 2 Br 5 NCs with high PLQY by reducing the trap density.…”
Section: Introductionmentioning
confidence: 99%